Analisis Kadar Protein Dan Tingkat Kesukaan Nugget Ikan Gabus Dengan Penambahan Tepung Wortel - Yulianti, Yulianti; Mutia, Khairun (Gorontalo Agriculture Technology Journal, 2018)
Snakehead fish one species of freshwater having high protein content. In addition snakehead fish has a lot of meat and white so that it can be processed into products such as nuggets. The addition of carrot flour nuggets in processing aims to increase the nutritional value and reduce the use of a binder such as flour. This research uses the method developed consists of two phases,Â  in the first making carrot flour and the second phase of making nuggets snakehead fish with formulation flour carrot (20g , 30g, 40g) , tapioca flour ( 80g , 90g, 70g) and wheat flour (50g, 30g, 40g). Data analysis using a completely randomized design (CRD) with three time test. The results snakehead fish nuggets are a high protein content from 16.03 to 24.7% and and favored by the panel both in terms of taste, color, aroma and texture.Â Keyword : snakehead fish, nugget, carrot